Accumulation Crisis and Global Police State. (September 2019) - Robinson, William I.
Global police state refers to three interrelated developments. First are the ever more omnipresent systems of mass social control, repression, and warfare promoted by the ruling groups to contain the real and the potential rebellion of the global working class and surplus humanity. Second is how the global economy is itself based more and more on the development and deployment of these systems of warfare, social control, and repression simply as a means of making profit and continuing to accumulate capital in the face of stagnation – what I term militarized accumulation, or accumulation by repression – and that now goes well beyond military Keynesianism. And third is the increasing move towards political systems that can be characterized as 21st century fascism, or even in a broader sense, as totalitarian. Digitalization makes possible the creation of a global police state. The mounting crisis appears to cement the emerging digital economy with the global police state. There is a triangulation of far-right, authoritarian, and neo-fascist forces in civil society, reactionary political power in the state, and transnational corporate capital, especially speculative finance capital, the military–industrial–security complex, and the extractive industries – all three interwoven with high-tech or digital capital.